An Autopsy-Based Study for Determination of Sex from the Length of Manubrium in the Central India Indore Region (M.P.) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Skeletol remains or decomposed bodies are an important initial step in forensic investigation. Accurate determination of skeletal sex has been a critical issue in medico-legal cases and the accuracy depends on the nature of material available and methods applied. Sternum is a bone which is easily retrievable even from the advance decomposed body and also from the bundle of bones so it becomes very important bone for age and sex determination in the advanced stage of decomposition and from mutilated, fragmented bodies. Total 632 subjects, consisting of 350 males and 282 females above the age of >25 years were taken in our study and data analysis was done by using SPSS software and relevant statistical test was applied. In our study, bisexual variation in relation to length of manubrium was found conclusive.
Keywords: Anthropometry; Bisexual variation; Bisexual variation Sex determination; Sternum manubrium; Length; SPSS software; Skeleton remain